IMPLEMENTATION OF THE WAKALAH WAL MURABAHAH CONTRACT AT PT PNM MEKAAR MEULABOH BASED ON DSN-MUI FATWA NO. 04/DSN-MUI/IV/2000 - Anggraini, Reska Aji; Hendrawan, Yoni; Ananda, M. Aditya; Rizki, Darlin (istinbath, 2025)
This study aims to analyse the implementation of the wakalah wal murabahah contract in the Islamic microfinance program of PT Permodalan Nasional Madani (PNM) Mekaar, Meulaboh Branch, located in Pasi Mesjid Village, West Aceh, with reference to the provisions of the National Sharia Board Indonesian Ulema Council (DSN-MUI) Fatwa No. 04/DSN-MUI/IV/2000. The Mekaar program empowers underprivileged women through group-based, collateral-free business capital financing, accompanied by business mentoring. This research adopts a qualitative case study approach, employing observation, in-depth interviews, and document analysis of the financing contracts. The findings reveal that financing through the wakalah wal murabahah scheme generally increases income and fosters microenterprise independence. However, several practices were inconsistent with Sharia principles, including executing the murabahah contract before the goods were legally owned by the institution and disbursing cash without a clear separation between the wakalah and murabahah stages. Such practices risk transforming the contract into a disguised qardh (loan), thereby contravening the principles of fiqh al-mu'amalah. These findings highlight the importance of separating contract stages into their respective pillars (arkan) and conditions (shurut), ensuring the institution's legitimate ownership of goods prior to the murabahah contract, issuing invoices in the institution’s name, and providing continuous Sharia education for staff and clients. The study recommends that PT PNM Mekaar enhance its Sharia compliance mechanisms by ensuring clear separation between wakalah and murabahah stages, issuing invoices in the institution’s name, and providing continuous Sharia education for both officers and clients. These measures are expected to improve transparency, fairness, and adherence to DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000.